Вплив автомобільних доріг на екобезпеку комплексу «автомобіль-дорога-середовище» - Внукова, Наталія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2011)
It was analased highway influence on the environment at all stages of life cycle, proposed the concept of air quality management algorithm for in the intensive traffic